2019
DOI: 10.4274/jcrpe.galenos.2019.2018.0098
|View full text |Cite
|
Sign up to set email alerts
|

No Associations Between Serum Lipid Levels or HOMA-IR and Asthma in Children and Adolescents: A NHANES Analysis

Abstract: Objective:Studies have reported inconsistent results on the associations between lipids and insulin resistance (IR) and asthma. The purpose of this study was to examine the associations between abnormal serum lipid levels and homeostatic model assessment-IR (HOMA-IR) and the presence of current asthma in children and adolescents.Methods:The United States National Health and Nutrition Examination Survey database from 1999 to 2012 was randomly searched for children (aged 3-11 years) and adolescents (aged 12-19 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…In the study, some 3703 asthmatics and 20,138 nonasthmatics were identified in the United States National Health and Nutrition Examination Survey database between 1999 and 2012. That study found no relationship between HOMA > 3 and asthma diagnosis [71], although it did not analyse the synergic action of obesity + insulin resistance that Forno et al had found [69]. Nevertheless, all those studies are crosssectional, so it is not possible to establish a causal relationship between obesity, insulin resistance and asthma.…”
Section: The Role Of Adipokines and Insulin Resistancementioning
confidence: 92%
“…In the study, some 3703 asthmatics and 20,138 nonasthmatics were identified in the United States National Health and Nutrition Examination Survey database between 1999 and 2012. That study found no relationship between HOMA > 3 and asthma diagnosis [71], although it did not analyse the synergic action of obesity + insulin resistance that Forno et al had found [69]. Nevertheless, all those studies are crosssectional, so it is not possible to establish a causal relationship between obesity, insulin resistance and asthma.…”
Section: The Role Of Adipokines and Insulin Resistancementioning
confidence: 92%
“…[3,4] The prospective cohort study in children born to mothers with a doctor's diagnosis of asthma has demonstrated the increased airway obstruction in children with high LDL-C. Children with high HDL-C had better lung function and less bronchial responsiveness [3]. While a recent epidemiologic study in China found no associations between serum lipid levels and pediatric asthma [4]. Non-HDL-C and the TG/HDL-C ratio are practical addition lipid measures in evaluating dyslipidemia in children [5].…”
Section: Introductionmentioning
confidence: 99%
“…The prospective cohort study in children born to mothers with a doctor's diagnosis of asthma has demonstrated the increased airway obstruction in children with high LDL-C. Children with high HDL-C had better lung function and less bronchial responsiveness [2]. While a recent epidemiologic study in China found no associations between serum lipid levels and pediatric asthma [3]. Non-HDL-C and the TG/HDL-C ratio are practical addition lipid measures in evaluating dyslipidemia in children [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is recently con icting evidence on the association between dyslipidemia and asthma [2,3]. The prospective cohort study in children born to mothers with a doctor's diagnosis of asthma has demonstrated the increased airway obstruction in children with high LDL-C. Children with high HDL-C had better lung function and less bronchial responsiveness [2].…”
Section: Introductionmentioning
confidence: 99%